Sexual behaviours among youth with disabilities in South Africa (2017): a cross-sectional analysis of levels, and the demographic and socioeconomic associated factors - Nkwanyana, Sinenhlanhla Jessica (My University, 2021)
BACKGROUND Globally, in public health, there is much attention given to sexual and reproductive health (SRH) for people with disabilities. Sexual risk behaviours play an important role in SRH. They are major indicators of sexually transmitted infections such as Human immunodeficiency virus, among other negative sexual health outcomes. South Africa is no exception to this reality, the country accounts for the highest portion of the global HIV/AIDS epidemic, including individuals with HIV/AIDS and a high incidence of infection rates. Due to the high prevalence of HIV/AIDS, research has identified disabled persons to be at risk for HIV/AIDS. However, the sexual behaviours of disabled youths in South Africa remain a neglected area. Youths are recognised as the core of sustainable development, with great potential to eradicate poverty, and encourage good health and wellbeing, attain good quality education, and contribute positively to the economy. OBJECTIVE The two set objectives of this study were; firstly, to examine levels of sexual behaviours by type of disability among disabled youth. Secondly, to identify the demographic and socioeconomic characteristics associated with sexual behaviours among youth with disabilities in South Africa in the year 2017. METHODOLOGY This study utilized data from the fifth South African National HIV, Behaviour and Health Survey of 2017 – this was the latest survey available. The sample for the study was people with disabilities who were sexually active and aged 15-34 years. The selection of a sample of those aged 15-34 years was due to the availability of complete sexual history. It was also helpful for categorisation purposes. The weighted sample of 88.019 was selected for the study which comprised people with disabilities who are sexually active and aged 15-34 years. Descriptive and analytical analyses were conducted, including cross-tabulations and binary logistic regression model. These were used to examine the demographic and socio-economic associated factors and sexual behaviours between the most recent sexual partners of the sample. The survey asked the participants about their sexual history, including if they had ever had sex, sexual activity in the past 12 months, age at first sex, condom use, and multiple sexual partnerships in the 12 months preceding the survey. RESULTS The majority of the study sample had a physical disability (54%), and the least were those with a speech disability (2%). The rates of being sexually active in the past 12 months were lowest among those who were aged 15-19 (61 per 1000 disabled youth) and highest among 30-34 years old youth (354 per 1000 disabled youth). Having sexual intercourse below, the legal South African consent age was highest among aged 30-34 years (207 per 1000 disabled youth). Using a condom at last sex was highest among youth aged 25-29 years (175 per 1000 disabled youth) while having two or more sexual partners was highest among those who were aged 30- 34 years (88 per 1000 disabled youth) and lowest among disabled youth aged 15-34 (0 per 1000 disabled youth). Youth with a mental disabilities had lesser odds of using a condom at last sex and having multiple sexual partners having multiple sexual partners. Disabled men had increased odds of using a condom at last sex and having two or more sexual partners, whilst disabled females were less likely to use a condom at last sex and were less likely to engage in multiple sexual partnerships in the past 12 months. CONCLUSION The hypothesis for this research was that there is no association between demographic and socio-economic factors and sexual behaviours among disabled youth in South Africa. The binary logistic regression indicated significant results. Therefore, the null hypothesis can be rejected and the alternative hypothesis that a possible relationship exists between demographic and socio-economic factors and sexual behaviours among youth with disabilities in South Africa can be accepted. Engaging in sexual intercourse is most likely among disabled youth with incorrect HIV knowledge. To ensure disability inclusiveness the disabled person's organizations need to ensure that youth's sexual behaviours are catered for in sexual health services, also in alignment with the National Strategic Plan 2017-2022 that aims for equal rights of a disabled person in sexual and reproductive health.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Arts in Health Demography to the Faculty of Humanities, University of the Witwatersrand, 2021
Keywords: Youth sexual behaviour; Youth with disability; Sexually transmitted infections; Human immunodeficiency virus